The memory of love : Sūrdās sings to Krishna - Sūradāsa, 1483?-1563? (Oxford University Press, 2009)
No Hindu god is closer to the soul of poetry than Krishna, and in North India no poet ever sang of Krishna more famously than SurdD=as-or Sur, for short. He lived in the sixteenth century and became so influential that for centuries afterward aspiring Krishna poets signed their compositions orally with his name. This book takes us back to the source, offering a selection of Surdas's poems that were known and sung in the sixteenth century itself. Here we have poems of war, poems to the great rivers, poems of wit and rage, poems where the poet spills out his disappointments. Most of all, though.